Constructing the Support as a Microreactor and Regenerator for Highly Active and In Situ Regenerative Hydrogenation Catalyst. (18th March 2021) - Zhao, Guoqiang; Liu, Tian; Wu, Binbin; Chen, Baoliang; Chu, Chiheng
Abstract: The demands for efficient and robust heterogeneous hydrogenation catalysts have triggered extensive research to optimize the structures of metal catalytic centers, but the potential of support construction for enhanced hydrogenation performance has been overlooked. This study introduces a hierarchically ordered porous poly(2, 6‐diaminopyridine) (PDAP) as a Pd nanoparticle support for hydrogenation removal of recalcitrant pollutants in water purification. The PDAP support acts as a sorbent and microreactor to enhance the proximity of targeted water pollutants and reactive hydrogen atom species, achieving unprecedently high water purification efficiency. The PDAP support also acts as a catalyst in mediating peroxide‐activation for oxidative destruction of Pd poisons (e.g., reduced sulfur), achieving in situ regeneration of poisoned Pd catalysis centers. The high activity and in situ regenerativity achieved by rational construction of the support structure sheds light on a new approach for designing efficient and robust heterogeneous hydrogenation catalysts. Abstract : This study introduces hierarchically ordered porous poly(2, 6‐diaminopyridine) (PDAP) as a Pd nanoparticle support for hydrogenation removal of recalcitrant pollutants during water purification. The PDAP support acts as a sorbent and microreactor to enhance the proximity of targeted water pollutants and reactive hydrogen atom species. The PDAP support also acts as a catalyst in mediating peroxide activation for oxidative destruction of Pd poisons.